A Comparative Evaluation of the Lagos and IIUM Models of Islamic Teacher Preparation - Saheed Ahmad Rufai (UIN Sultan Aji Muhammad Idris Samarinda, 2021)
The Muslim world has witnessed the emergence of several Islamic-based institutes and universities in the last four decades, in keeping with some of the recommendations of the World Conferences on Muslim Education. Yet there has not been a comprehensive study of the system as operated in various contemporary Muslim settings, with a view to assessing the degree of its adequacy and efficacy. The purpose of this paper is to carry out a comparative evaluation of the Bachelor’s degree in Islamic Education programmes of the International Islamic University Malaysia (IIUM) and the University of Lagos in Nigeria. The choice of the two educational settings was informed by the impression that Malaysia offers some of the best practices in Islamic education, which may be used as standards in benchmarking for Islamic education in Nigeria, an African country with the largest Muslim population. The significance of such a study lies in its potentiality to expose the strengths and deficiencies of each of the models, as well as highlight their commonalities and differences with regard to educational aims, curricula, structures, teaching methods, and evaluation procedures. The paper is guided by three research questions seeking to elicit information or generate data about the nature of the two models being evaluated, the comparative strengths and weaknesses of the two models, and ameliorative propositions with potential to enrich or enhance the quality of the two models. The paper employs curriculum criticism and the analytic method in its comparative evaluation. The significance of the paper lies in its ameliorative propositions for curriculum enrichment purposes, aimed at making the two models better and of merit.